Atomic rare earths activate direct O-O coupling in manganese oxide towards electrocatalytic oxygen evolution - Li, Meng (2024)
Activating the efficient electron transfer in oxygen evolution reaction (OER) by tuning the oxygen (O) electronic states near the Fermi level is essential to break the linear scaling limitation of OER intermediates. Herein, we construct a series of rare earth (RE) single atoms on MnO2 nanosheets with modulated oxygen states by an effective and universal Ar plasma (P)-assisted strategy (P-RE SAs@MnO2, RE = Gd, La, Ce, Tm, and Lu) to investigate the origin of RE-enhanced OER performance. Taking P-Gd SAs@MnO2 as a representative, the atomically dispersed Gd atoms on MnO2 assist the construction of localized asymmetric [Gd−O−Mn] units, which induces electron accumulation at surrounding oxygen sites by introducing the polarized ionic Gd−O bond. As a result, the P-Gd SAs@MnO2 delivers impressive OER performance with low overpotential (281 mV@10 mA cm −2; ηj10), robust long-term stability, and optimized activation energy (Ea = 32.07 kJ mol−1 at ηj10), which are superior to RE-free MnO2, commercial RuO2, and most Mn-based catalysts. Similar enhanced OER performance can also be found for other P-RE SAs@MnO2 (RE = La, Ce, Tm, and Lu). X-ray absorption and in situ Raman spectroscopy unveil the preferred electron accumulation at Mn−O, promoting the formation of terminal MnIV=O intermediates in OER. Theoretical calculations demonstrate that the construction of [Gd−O−Mn] unit endows the surface lattice unsaturated O site with the labile property, which assists the direct formation of (O−O) dimer for circumventing the universal scaling relation applied by the formation of *OOH. This work opens up a new avenue for the design of transition metal oxides with modulated oxygen state to break the limitation of the adsorbate evolution mechanism during OER.